Environmental Learning Insights from research into the student experience - Rickinson, Mark.; Lundholm, Cecilia; Hopwood, Nick.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Environmental education and education for sustainable development have become features of many countries$1 (Bformal education systems. To date, however, there have been few attempts to explore what such learning looks and feels like from the perspective of the learners. Based on in-depth empirical studies in school and university classrooms, this book presents rich insights into the complexities and dynamics of students$1 (Benvironmental learning. The authors show how careful analysis of students$1 (Benvironmental learning experiences can provide powerful pointers for future practice, policy and research. Environmental Learning will be a key resource for educators, teacher educators, decision-makers and researchers involved in education and sustainable development.s
What Is Environmental Learning? -- Researching Environmental Learning -- Lenses for Understanding Environmental Learning -- Dealing with Emotions and Values -- Questioning Relevance -- Negotiating Viewpoints Among Students and Teachers -- Enhancing Environmental Learning -- Erratum.
Keywords: Education; Curriculums (Courses of study).; Education -- Curricula; Teaching; Environment; Sustainable development; Education; Education, general; Learning & Instruction; Curriculum Studies; Teaching and Teacher Education; Environment, general; Sustainable Development; Electronic books